Diabetic foot syndrome in patients with diabetes. A multicenter German/Austrian DPV analysis on 33 870 patients. Issue 6 (1st June 2018) - Bohn, Barbara; Grünerbel, Arthur; Altmeier, Marcus; Giesche, Carsten; Pfeifer, Martin; Wagner, Christian; Heise, Nikolai; Best, Frank; Fasching, Peter; Holl, Reinhard W.
Abstract: Aims: The diabetic foot syndrome (DFS) is a serious complication in patients with diabetes increasing the risk for minor/major amputations. This analysis aimed to examine differences in diabetes patients with or without DFS stratified by type 1 (T1D) or type 2 diabetes (T2D). Material and Methods: Adult patients (≥20y of age) with diabetes from the German/Austrian diabetes patients follow‐up registry (DPV) were included. The cross‐sectional study comprised 45 722 subjects with T1D (nDFS  = 2966) and 313 264 with T2D (nDFS  = 30 904). In DFS, minor/major amputations were analysed. To compare HbA1C, neuropathy, nephropathy, cardiovascular disease risk factors, and macrovascular complications between patients with or without DFS, regression models were conducted. Confounders: age, sex, diabetes duration. Results: In patients with DFS, a minor amputation was documented in 27.2% (T1D) and 25.9% (T2D), a major amputation in 10.2% (T1D) and 11.3% (T2D). Regression models revealed that neuropathy was more frequent in subjects with DFS compared with patients without DFS (T1D: 70.7 vs 29.8%; T2D: 59.4% vs 36.9%; both P  < 0.0001). Hypertension, nephropathy, peripheral vascular disease, stroke, or myocardial infarction was more common compared with patients without DFS (all P  < 0.0001). In T1D with DFS, a slightly higher HbA1C (8.11% vs 7.95%; P  < 0.0001) and in T2D with DFS a lower HbA1C (7.49% vs 7.69%; P  < 0.0001) was observed. Conclusions: One third of the patients with DFS had an amputation of the lower extremity. Especially neuropathy or peripheral vascular disease was more prevalent in patients with DFS. New concepts to prevent DFS‐induced amputations and to reduce cardiovascular risk factors before the occurrence of DFS are necessary.